2019
DOI: 10.1017/s0140525x18002029
|View full text |Cite
|
Sign up to set email alerts
|

Beyond uncertainty: A broader scope for “incentive hope” mechanisms and its implications

Abstract: We propose that food-related uncertainty is but one of multiple cues that predicts harsh conditions and may activate “incentive hope.” An evolutionarily adaptive response to these would have been to shift to a behavioral-metabolic phenotype geared toward facing hardship. In modernity, this phenotype may lead to pathologies such as obesity and hoarding. Our perspective suggests a novel therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our findings of poorer sleep quality and elevated insomnia symptoms in individuals with OCD and HD compared with healthy controls have important clinical implications. First, for individuals with HD and OCD experiencing disordered sleep, sleep disturbances may increase functional impairment and hinder effective treatment through negative effects on cognition and emotion regulation (Deliens et al, 2014;Durmer and Dinges, 2005;Krystal et al, 2008;Linkovski et al, 2019;Ramsawh et al, 2009). We suggest that screening for sleep disturbances may influence treatment of choice and impact treatment response among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of poorer sleep quality and elevated insomnia symptoms in individuals with OCD and HD compared with healthy controls have important clinical implications. First, for individuals with HD and OCD experiencing disordered sleep, sleep disturbances may increase functional impairment and hinder effective treatment through negative effects on cognition and emotion regulation (Deliens et al, 2014;Durmer and Dinges, 2005;Krystal et al, 2008;Linkovski et al, 2019;Ramsawh et al, 2009). We suggest that screening for sleep disturbances may influence treatment of choice and impact treatment response among patients.…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, the current study showed that certain stimuli or situational factors can influence whether we will successfully overcome unwanted behaviors, thoughts, or emotions [ 73 ]. First, we showed that when individuals with OCD encounter symptom-provoking stimuli, their inhibitory control becomes less efficient than when they encounter neutral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may test the impact of inhibitory control induction on behavioral manifestations of uncertainty in different patient populations, possibly informing us on unwanted thoughts and behaviors’ converging and diverging pathways ( Linkovski, Weinbach, et al, 2019 ). Others may test our predictions using different trial proportions in our paradigm or test our hypotheses with different uncertainty tasks while inducing differential uncertainty levels.…”
Section: Discussionmentioning
confidence: 99%